Customer-centric brand promotion model: operational excellence of import-export in the food industry - Jeremiah Palmiano; Rejoice Ferrer; Chiqui Umali; Ryan Romnick Sanchez; Mary Anne Rhoda Pascua; Angelita Regala (Environment and Social Psychology, 2025)
This study addresses the critical importance of customer-focused strategies and brand promotion within the food component import–export sector, a context that remains underexplored, particularly with respect to the influence of external factors across diverse geographical settings. Its objective was to empirically investigate how operational excellence, particularly customer relationship management (CRM), value-added services, and product quality and safety assurance affects customer loyalty and, in turn, drives brand promotion. Utilizing a descriptive quantitative research design, a cross-sectional survey was administered in the Philippines, with data analyzed through Structural Equation Modeling (SEM). The findings indicate that CRM exerts the most significant influence on customer loyalty, while product quality and safety assurance also positively contributes. Importantly, customer loyalty emerged as a strong driver of brand promotion. The model demonstrated high predictive power for customer loyalty and substantial explanatory power for brand promotion. These results highlight that strong customer relationships developed through CRM are essential for fostering loyalty and positioning customers as effective brand advocates. Preserving product quality and safety assurance is fundamental, the study’s results imply that companies should purposefully put in comprehensive CRM systems and tailored encounters. To develop devoted clients, hence boosting brand awareness and securing sustained competitive advantage. Future studies ought to broaden the scope of investigated factors and explore more generalizable geographical settings to improve generalizability.